2020
DOI: 10.1186/s13229-020-00375-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced social learning of threat in adults with autism

Abstract: Background Recent theories have linked autism to challenges in prediction learning and social cognition. It is unknown, however, how autism affects learning about threats from others “demonstrators” through observation, which contains predictive learning based on social information. The aims of this study are therefore to investigate social fear learning in individual with autism spectrum disorder (ASD) and to examine whether typically developing social cognition is necessary for successful observational learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…During the test phase, we replicated the general SFL effect (Espinosa et al, 2020; González‐Rodríguez et al, 2021) but also found an interaction between CS and group such that only healthy controls showed a higher SCR in response to the CS+ compared to CS−. This important result indicates significant learning in the control group and nonexistent learning in the patients with severe AUD.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…During the test phase, we replicated the general SFL effect (Espinosa et al, 2020; González‐Rodríguez et al, 2021) but also found an interaction between CS and group such that only healthy controls showed a higher SCR in response to the CS+ compared to CS−. This important result indicates significant learning in the control group and nonexistent learning in the patients with severe AUD.…”
Section: Discussionsupporting
confidence: 79%
“…This might account for the observed tendency toward an interaction between group and CS type during the test phase. However, we can note that the large effect size on which we based our sample size calculations was based on a study involving individuals with autistic disorder (Espinosa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, threat and safety information is socially communicated by observing the actions and experiences of others or through verbal instructions (e.g., Bandura & Walters, 1977;Olsson & Phelps, 2007). Such social learning processes provide important, but rarely studied, information on the emergence, maintenance, and treatment of (anxiety) psychopathology (Espinosa et al, 2020;Muris & Field, 2010;Schellhaas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Social anxiety has also been found to be associated with excessive deliberation 41 and with suboptimal learning 42 . Finally, autism has been linked to deficits in behavioral adaptation during social inference, specifically suboptimal flexibility and lower mentalizing sophistication 43 , overestimation of the volatility of sensory environment 44 , reduced implicit causal inference about sensory signals 45 , and enhanced observational learning in the aversive domain 46 . Therefore, we hypothesized that anxiety, as well as social dysfunctions associated with autism and social anxiety are likely to be sensitive to the computational heterogeneity in strategy use during EL, OL, and the arbitration between them.…”
Section: Introductionmentioning
confidence: 99%